SERVICE QUALITY USING DIGITAL MARKETING BASED ON STARTUPS FOOD AND BEVERAGE COMPANY IN SLEMAN YOGYAKARTA - Dodi Setiawan Riatmaja; Sigit Wibawanto; Erlita Ridanasti (Journal of Digital Business and Management, 2022)
The purpose of this study was to determine the effect of service quality using digital marketing based on consumer satisfaction for startup food and beverage companies in Sleman Yogyakarta. This research was conducted by taking 88 customers of startups food and beverage in Yogyakarta randomly. The calculation technique used in this study is the Multiple Linear Regression Analysis model and path analysis. Based on the results of the analysis, it shows that there is a significant influence between the use of digital marketing services on consumer satisfaction in terms of service. The results of multiple linear regression analysis show that there is a positive and significant effect of the dimensions of direct evidence, reliability, responsiveness, assurance, and empathy simultaneously on consumer satisfaction at startups food and beverage companies in Yogyakarta. That is, tangibles, reliability, responsiveness, assurance, and empathy have been able to make a significant contribution in increasing customer satisfaction at startups food and beverages in Yogyakarta.